GoldenharSyndrome: Case Report and literature revision - Correa-Olaya, Eufemia Isabel (2013)
Goldenhar syndrome is the second most frequent craniofacial malformation; occur sporadically or as an autosomal-dominant inheritance that involves derivatives of the first and second branchial arch. Furthermore, an association with exposure to different drugs and maternal diabetes has been described. Main features are eye conditions, headphones (ear, pinna) and vertebral, hence its nickname spectrum oculo-auriculo-vertebral. We report the case of a girl of eight years old with multiple congenital anomalies by a multidisciplinary study will highlight the clinical features suggestive of this syndrome. The results were satisfactory for the patients, it was dental treatment and hard tissue distraction osteogenesis of the mandible at the Instituto Nacional de Salud del Niño.